PERKEMBANGAN KEMAMPUAN ASPEK KOGNITIF PESERTA DIDIK DALAM PROSES PEMBELAJARAN - Ismail, Ibrahim (Musawa: Journal for Gender Studies, 2020)
Cognitive development is one of students' development aspects related to knowledge. It inlcudes all psychological processes related to individual's method to learn and comprehend his environment. Cognitive development is a development step of human from child to adult, from concrete thinking process to the advanced ones, which is abstract and covering logical concepts. Cognitive development in children is their abilities to think in a more complicated way, do reasoning, and solve problems that include into psychological process related to an individual's method of learning and taking his environment into account. The characteristics of students' cognitive development have to be realized by all parties. With the comprehension of the characteristics of students' cognitive development, teachers and parents can determine the development limit the students had according to their age, so teachers and parents can implement the knowledge that suits children’s cognitive skill.